RETORIKA QUR’ANI SEBAGAI INTSRUMEN DAKWAH : ANALISIS TEMATIK AYAT-AYAT TARGHIB WA TARHIB - Samah Umi Mujahidah; Ahmad Isnaeni; Budimansyah (Studia Quranika, 2025)
The declining effectiveness of Islamic preaching in the modern era indicates the need for a communicative approach that engages both the rational and emotional dimensions of human beings. In this context, the Qur’an offers a powerful rhetorical framework through the concepts of targhīb (motivation and promise) and tarhīb (warning and deterrence) as persuasive instruments of da‘wah. This study aims to analyze the role of Qur’anic rhetoric in verses containing targhīb and tarhīb as a method of preaching capable of fostering moral and spiritual awareness within contemporary society. Employing a qualitative method based on thematic exegesis (tafsir maudhu‘i), this research systematically identifies, classifies, and analyzes relevant verses to uncover their rhetorical patterns and ethical messages. The findings reveal that Qur’anic rhetoric integrates logical reasoning, aesthetic expression, and spiritual depth in conveying divine guidance effectively. Verses of targhīb cultivate hope, optimism, and moral transformation through promises of divine mercy and reward, while verses of tarhīb reinforce ethical responsibility through reminders of accountability and punishment. The synergy between these two elements produces a balanced model of preaching that harmonizes hope and caution, shaping reflective and morally grounded individuals. This study affirms the continued relevance of Qur’anic rhetoric as a foundation for developing contextual, humane, and communicative models of da‘wah in response to contemporary social change.